استخدام أسلوب تخمين الكلمة لتنمية استيعاب المفردات لدى طلاب الفصل الثاني بالمدرسة الثانوية الإسلامية الحكومية 11 فيدي - Abdi Aziz, Miswarul (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2024)
Abstrac This research aims to determine the students response after applying the word guessing technique in vocabulary teaching at State Islamic senior high school 11 Pidie, and to determine whether using the word guessing technique enhances the ability of second-year students at state Islamic senior high school 11 Pidie. The research method employed by the researcher is an exsperimental approach with a pre-test and post-test design for a single group. The data collection methods used by the researcher include observation questionnaires tests and documentation. The results of the study show that students responses to vocabulary teaching after using the word guessing technique indicate a high level of enthusiasm. the word guessing technique motivates students to learn vocabulary actively, creatively, and enjoyably. Furthermore, the use of the word guessing technique is effective and influential in enhancing students vocabulary comprehension ability at state Islamic senior high school 11 pidie, as evidenced by the t-test result (negative) being smaller than the t-table value (negative), or (-8.703<-1.753).